A methodology for determining Air Force Education Requirements Board (AFERB) advanced academic degree (AAD) requirements - Terry, Tara.; Robbert, Albert A., 1944-; Boon, John, 1959-; Firoz, Perry Shameem; Moore, S. Craig, 1946-; Project Air Force (U.S.). Manpower, Personnel, and Training Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 2013)
United States Air Force career field managers (CFMs) annually predict the number of billet vacancies that will require an officer who holds an advanced academic degree (AAD), and submit these requirements to the Air Force Education Requirements Board to fill the projected vacancies. The process requires CFMs to predict specific vacancies three to five years before they occur, which can be difficult and produces inaccuracies that can lead to a shortfall of officers qualified to fill positions that require an AAD or to an oversupply of officers with AADs, which unnecessarily increases Air Force costs. This report examines the Air Force process for producing, allocating, and assigning officers with master$1 (Bs and doctorate degrees. The authors find that a relatively low percentage of officers with master$1 (Bs or doctorate degrees were matched to a billet that requires that degree and academic specialty in fiscal years 2000 through 2010. The authors provide a methodology for determining the required production level of officers who earn AADs, and this report serves as a user$1 (Bs guide for the modeling tools that illustrate the methodology.s
Introduction -- Outcomes of the Current AAD Process: Analysis of Officers Earning Advanced -- AAD Production Requirements Model -- Conclusions and Recommendations -- Appendix: AAD Production Calculation Example.
"RAND Project Air Force."
"This work was ... conducted within the Manpower, Personnel, and Training Program of RAND Project Air Force"--Preface.
Includes bibliographical references (p. 39).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Officers -- Education (Higher); United States. -- Air Force -- Officers -- Promotions; United States. -- Air Force -- Personnel management; United States. -- Air Force Academy